Gating as exclusionary commoning in a post-socialist city: Evidence from Gdansk, Poland - Maja Grabkowska; Magdalena Szmytkowska (REGION, 2021)
New-build gated condominiums at the periphery of a post-socialist city are a well-studied phenomenon. However, in Poland, recent years have seen an expansion of residential gating into old inner-city neighbourhoods and socialist large housing estates. The resulting fragmentation and privatisation of public space have raised much controversy and debate on appropriation of urban common good. This paper presents outcomes of a research on the changing discourse of gating in Gdansk, based on a discourse analysis of newspaper articles and interviews with key urban stakeholders. On the one hand, gating is seen as an anti-commoning practice criticised for its elitist character and undesirable socio-spatial consequences. On the other, a narrative of exclusionary commons has emerged to justify the need of gating in specific cases. Considering the varying motivations and types of gating in different urban areas, the authors have attempted a classification, relating gating practices to commoning strategies and their justification in localities typically characterised by atomistic individualism and social disintegration.
Keywords: 330; Gating; urban commons; common good; post-socialist city; Gdansk